Synthesis, characterization, and assessment of the antimicrobial activity of MgO – calcium alginate porous beads - Cedeño-Matte, Yarilyn (2016)
The dispersion of antibacterial nanoparticles into bio-compatible, non-toxic and bio-degradable polymeric matrices will enable the development of more efficient and effective materials for food preservation, removal of contaminants, and protection against human health-compromising microorganisms. Nanometric bactericidal materials have a very large surface to volume ratio that enable them to attach more copies of biological molecules, and hence, enhance antimicrobial efficiency. More recently, the antimicrobial activity of environmental-friendly and chemically stable MgO has been suggested. The incorporation of bactericidal compounds into a polymeric matrix can combine physical stability provided by the polymeric matrix with the antimicrobial properties of antimicrobial agents dispersed as solid tiny particles. On this basis, the present research will be focused on the development of biocompatible polymer-inorganic particle mixtures, so-called nanocomposites, with tunable and enhanced antimicrobial activity. The antimicrobial activity of calcium alginate – MgO beads (ranging from 0% - 40% w/w MgO) against E. coli was confirmed. Beads containing 20% w/w of MgO fully inhibited the E. coli. bacterial growth.